Flexible pentacene organic field-effect phototransistor - Yakuphanoğlu, Fahrettin; Farooq, W. Aslam (Elsevier Science Sa, 2011)
A photoresponsive organic field-effect transistor was fabricated on indium tin oxide deposited onto polyethersulphone flexible substrate with pentacene as the active material and poly(4-vinyl phenol) as the dielectric material. The mobility, threshold voltage and maximum number of interface traps for the pentacene-OTFT under dark, UV and white light illuminations were found to be 2.22 x 10(-1) cm(2)/V s, 12.97V, 1.472 x 10(13) eV(-1) cm(-2) and 2.93 x 10(-1) cm(2)/Vs.14.84 V, 1.431 x 10(13) eV(-1) cm(-2) and 2.95 x 10(-1) cm(2)/V s.17.70 V, 1.447 x 10(13) eV(-1) cm(-2), respectively. The phototransistor under UV and white illuminations exhibits a high photosensitivity in the off state. The obtained results indicate that the flexible pentacene transistor could be potentially used in photodetectors by a white light and UV optical gate. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic thin film transistor; Pentacene; Thermal evaporation